Ways of improving of freight car design (Transport systems and technologies, 2024)
The article presents the dynamics of freight cars production by domestic enterprises by years. The necessity of renewal of the domestic operating fleet of freight cars.The following main vectors of design improvement have been identified based on the results of putting new and modified freight car models into production: use of high-strength steels in load-bearing structural elements and innovative components; improving existing and creating fundamentally new bearing structures; the most efficient use of space; development of freight cars with an axle load of 25 tonnes; creation of multifunctional structures; increasing the structural strength of long-base flat cars; application of the latest assembly and welding technologies. The following main vectors for improving the design of cars have been identified based on the results of a analysis of scientific and applied research, in addition to the above: the use of new materials; development of six-axle articulated wagons with an axle load of 23.5 tonnes and 25 tonnes; development of railcars using new generation bogies and components; achieving a uniform load on the supporting structure; design of flat cars for transporting containers in two tiers; development of new cars for intermodal, interoperable and combined transport.
Keywords: freight car; design; fleet; rolling stock; improvement